PENENTUAN KONSTANTA HUBBLE DENGAN MENGGUNAKAN SUPERNOVA Ia PADA PANJANG GELOMBANG INFRAMERAH DEKAT - Nazli, Ajraini
The determination of Hubble constant has been one of the central goal in observational astrophysics for nearly 100 years. Extraordinary progress achieved in recent years is based on two methods: distance ladder at low redshift and cosmological approch such as from Cosmic Microwave Background (CMB), at high redshift. Recent results have shown tension between these two methods. Therefore serious efforts have been put forward to minimize uncertainties in the determination of Hubble constant, especially on the distance ladder approach in which uncertainties in the lower rungs propagate to the higher ones using SN Ia in near-infrared (NIR). This Final Project reproduce the work of Dhawan et al. (2018), using SN Ia in NIR J-Band in distance ladder method to determine the Hubble constant. Two new SNe Ia are added to the calibrator sample and Cepheid periode-luminosity relation in LMC updated by Riess et al. (2019) is used in determining the distance modulus of SN Ia. SNe Ia data used in this Final Project are taken from Riess et al. (2016) for the calibrator sample and from various literature for Hubble flow sample. The SNe Ia were selected and the light curves were fitted using SnooPy package. No shape and color corrections were performed as is commonly done for optical light curves, due to small extinction in NIR. Employing Bayesian statistic the Hubble constant was determined with Markov Chain Monte Carlo (MCMC) method using Affine invariant algorithm. The determination of Hubble constant in this Final Project gives ????0=70,65?1,91+1,96 km/s/Mpc to ????0=75,12?1,98+2,05 km/s/Mpc, depending on the size of the calibrator sample and the luminosity-period relation used. The results are in 0,95? – 3,36? tension with the CMB determination by Planck collaboration (2018), i.e. ????0=67,37 ±0,54 km/s/Mpc.